Monitoring of unconventional oil and gas extraction and its policy implications: A case study from South Africa. (July 2018) - Esterhuyse, Surina; Avenant, Marinda; Redelinghuys, Nola; Kijko, Andrzej; Glazewski, Jan; Plit, Lisa; Kemp, Marthie; Smit, Ansie; Vos, A. Tascha
Abstract: Biophysical and socio-economic monitoring during unconventional oil and gas (UOG) extraction is important to assess change and to have reference conditions against which to identify UOG extraction activity impacts. The large-scale cumulative impacts of UOG extraction makes standardised monitoring across geographic and socio-political regions important. This article emphasises the importance of a robust monitoring framework that must serve as a guideline for planning monitoring activities during UOG extraction. A case study from South Africa is presented to illustrate important aspects to address during the development of a UOG extraction monitoring framework. The South African case is critically assessed and resultant policy implications are discussed. Important policy considerations include performing baseline monitoring during UOG extraction, performing UOG extraction monitoring in an integrated, systematic, and standardised manner, ensuring that proper resources are available to perform the monitoring and implementing an adaptive management plan that is linked to UOG extraction monitoring. Highlights: Unconventional oil and gas (UOG) extraction has biophysical and socio-economic impacts. UOG extraction monitoring can minimise impacts and assess change. We present a South African UOG extraction monitoring framework. We conclude that monitoring during all phases of UOG extraction is important. We emphasize that both biophysical and socio-economic aspects should be monitored.